Genealogy of the Transformation of Hifdzun Nasl Law: A Study of Classical and Modern Literature on Intellectual Property Rights in the Perspective of Al-Qurtubi - Ridwan, Ridwan; Munir, Akmal Abdul (Jurnal El-Thawalib, 2025)
Genealogy of the transformation of ḥifẓ al-nasl law from classical literature to the protection of Intellectual Property Rights (IPR) in the perspective of Al-Qurṭubī. ḥifẓ al-nasl, as one of the main objectives of the Shari'a in the theory of maqāṣid al-Syarī'ah, not only protects human biological continuity, but also emphasizes the moral, social, and intellectual dimensions. Through the classical approach developed by Al-Juwaynī, Al-Ghazālī, and Al-Syāṭibī, shari'a is understood as an instrument for achieving the benefit of the people (maṣlaḥah al-'ibād) by maintaining social dignity and stability. Tafsir Al-Qurṭubī emphasizes that the protection of descendants includes the honor, identity, and contribution of the individual, so that this principle can be adapted to the modern context, especially in the protection of intellectual works. The Islamic legal transformation approach (taḥawwul al-fiqh) explains the evolution of law from classical regulations regarding marriage, lineage, and inheritance to modern mechanisms that protect intellectual property rights (IPR), as a form of human "intellectual heritage." IPR theory from a contemporary perspective emphasizes that creative works have socio-moral values that must be protected, and that their violation constitutes ẓulm. The synthesis of the three theoretical frameworks—maqāṣid al-shari'ah, legal transformation, and IPR—provides a conceptual foundation for understanding the continuity of classical law in a modern context. This research demonstrates that IPR protection is a contemporary embodiment of the principle of ḥifẓ al-nasl, bridging classical and modern law, and affirming the relevance of the divine purpose of sharia in maintaining human sustainability, both biologically and intellectually